2016
DOI: 10.1063/1.4959573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NiO inserted layer on spin-Hall magnetoresistance in Pt/NiO/YIG heterostructures

Abstract: Articles you may be interested in

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…Since the effect is unaffected by magnetization reversal it would appear natural to observe it in antiferromagnetic multilayers (Manchon, 2017b). Indeed, it has been reported for several antiferromagnets: metallic IrMn in YIG/IrMn stacks , insulating SrMnO 3 in SrMnO 3 =Pt stacks , and insulating NiO in Pt/NiO/YIG trilayers (Shang et al, 2016;Hou et al, 2017;Hung et al, 2017;Lin and Chien, 2017).…”
Section: Spin Hall Magnetoresistancementioning
confidence: 94%
See 2 more Smart Citations
“…Since the effect is unaffected by magnetization reversal it would appear natural to observe it in antiferromagnetic multilayers (Manchon, 2017b). Indeed, it has been reported for several antiferromagnets: metallic IrMn in YIG/IrMn stacks , insulating SrMnO 3 in SrMnO 3 =Pt stacks , and insulating NiO in Pt/NiO/YIG trilayers (Shang et al, 2016;Hou et al, 2017;Hung et al, 2017;Lin and Chien, 2017).…”
Section: Spin Hall Magnetoresistancementioning
confidence: 94%
“…This effect was linked to enhanced spin Hall magnetoresistance at the magnetic phase transition of NiO (Hou et al, 2017;Lin and Chien, 2017). An unconventional negative signal was also detected (Shang et al, 2016;Hou et al, 2017;Lin and Chien, 2017). Hou et al (2017) suggested that this negative signal is due to spin-flop coupling (90°exchange coupling) between the NiO and YIG magnetic orders, whereas Lin and Chien (2017) linked the effect to spin-flip reflection from the NiO antiferromagnet exchange coupled with the YIG layer.…”
Section: Spin Hall Magnetoresistancementioning
confidence: 98%
See 1 more Smart Citation
“…The presence of thin layers of electrically insulating NiO is certain to affect charge and spin transport between the Ni and Pt particles. However, as NiO is antiferromagnetic, spin currents can still propagate through thin layers of this material; this has been demonstrated in several recent studies, one of which observed spin currents transmitted through NiO layers up to 100 nm thick in Y 3 Fe 5 O 12 /NiO/Pt heterostructures, as well as multiple studies that suggest the addition of NiO actually enhances the transmission of spin currents under certain conditions12272829. The presence of NiO undoubtedly has a detrimental effect on the electrical resistivity and power factor of both the reference and composite materials, although we anticipate these effects may be partially negated by a corresponding decrease in thermal conductivity.…”
Section: Resultsmentioning
confidence: 90%
“…These features allow one to use the SMR as a convenient means to extract the magnitude of spin Hall angle of the HM layer: the spin Hall angle obtained through SMR seem to agree with that estimated by other methods 9 . Recently, studies on SMR related effects have been increasing 10 ; an unidirectional component of the SMR is found in HM/FM bilayers 11 , SMR has been observed in systems with antiferromagnets [12][13][14][15] , the observation of the spin Nernst effect is based on the SMR theory [16][17][18] and the SMR analogue of the Rashba-Edelstein effect 19,20 has been found in Bi based structures 21 .…”
mentioning
confidence: 99%